2014
DOI: 10.1111/pme.12355
|View full text |Cite
|
Sign up to set email alerts
|

Overgeneral Autobiographical Memory in Patients with Chronic Pain

Abstract: The retrieval of AM in patients with chronic pain tends to be overgeneral and delayed, and the retrieval style of AM may be contributed to negative emotions and chronic pain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
2
20
1
Order By: Relevance
“…Interestingly, OAM are characteristic not only for people affected by depression, but they were also confirmed in patients with post‐traumatic stress disorder, among people considering suicide attempts, in patients with nutrition disorders, in people suffering from chronic pain and in people diagnosed with borderline personality disorder . The area of research over AM has been continuously expanding in recent years.…”
Section: Am In Recurrent Depressive Disordersmentioning
confidence: 90%
“…Interestingly, OAM are characteristic not only for people affected by depression, but they were also confirmed in patients with post‐traumatic stress disorder, among people considering suicide attempts, in patients with nutrition disorders, in people suffering from chronic pain and in people diagnosed with borderline personality disorder . The area of research over AM has been continuously expanding in recent years.…”
Section: Am In Recurrent Depressive Disordersmentioning
confidence: 90%
“…Following the Chinese version of the Autobiographical Memory Test (AMT) [26, 27], participants were asked to retrieve a specific memory to 12 given emotional cue words in Chinese. Cue words were presented orally in a fixed order, with six negative and six positive words alternating: guilty, successful, lonely, honest, sad, proud, horrible, brave, angry, interested, painful, and happy.…”
Section: Methodsmentioning
confidence: 99%
“…An influential study by Redelmeier and Kahneman (1996) demonstrated that patients' memories of the amount of discomfort reported after an acute minimally invasive procedure was determined primarily by the intensity of pain at both the procedure's worst and most recent episodes, a phenomenon now known as the “peak-end rule”. Memory biases have also been documented in chronic pain patients, with evidence that long-term pain is remembered less accurately than acute pain ( Linton and Melin, 1982 ; Salovey and Smith, 1997 ) and that people with persistent pain report intensity of previous pain less accurately than healthy people ( Liu et al, 2014a ). These inaccuracies in the recall of spontaneous episodes of chronic pain can become worse over time and even impact memories of treatment efficacy ( Feine et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%